Effects of interleukin‐1β and tumor necrosis factor‐α on macrophage inflammatory protein‐3α production in synovial fibroblast‐like cells from human temporomandibular joints. (18th January 2013) - Akutsu, Miwa; Ogura, Naomi; Ito, Ko; Kawashima, Mutsumi; Kishida, Tsuyoshi; Kondoh, Toshirou
<x xml:space="preserve">Abstract</x> Background Interleukin‐1β (IL‐1β) and tumor necrosis factor‐α (TNF‐α) are key mediators of the intracapsular pathological conditions of the temporomandibular joint (TMJ). Therefore, the gene expression profiles in synovial fibroblast‐like cells (SFCs) from patients with internal derangement of the TMJ were examined after they were stimulated with IL‐1β or TNF‐α to determine which genes were altered. Methods Ribonucleic acid was isolated from SFCs after IL‐1β or TNF‐α treatment. Gene expression profiling was performed using oligonucleotide microarray analysis. On the basis of the results of this assay, we investigated the kinetics of macrophage inflammatory protein‐3α (MIP‐3α) gene expression using PCR, and protein production in TMJ SFCs stimulated by IL‐1β or TNF‐α using an ELISA. Inhibition experiments were performed with MAPK and NFκB inhibitors. SFCs were stimulated with IL‐1β or TNF‐α after treatment with inhibitors. The MIP‐3α levels were measured using an ELISA. Results Macrophage inflammatory protein‐3α was the gene most upregulated by IL‐1β‐ or TNF‐α stimulation. The mRNA and protein levels of MIP‐3α increased in response to IL‐1β in a time‐dependent manner. In contrast, during TNF‐α stimulation, the MIP‐3α mRNA levels peaked at 4 h, and the protein levels peaked at 8 h. In addition, the IL‐1β‐ and TNF‐α‐stimulated MIP‐3α production was potently reduced by the MAPK and NFκB signaling pathway inhibitors. Conclusion Interleukin‐1β and TNF‐α increased the MIP‐3α production in SFCs via the MAPK and NFκB pathways. These results suggest that the production of MIP‐3α from stimulation with IL‐1β or TNF‐α is one factor associated with the inflammatory progression of the internal derangement of the TMJ.